Can we save the planet? : A Primer for the 21st Century - Bell, Alice (Thames & Hudson, 2020)
A topical, well-balanced and in-depth book that surveys thedetrimental impact humans have had on the planet over the last250 years, and evaluates what we can do to reverse the damage.